Ferric carboxymaltose in the management of anemia due to non-obstetric conditions in women: a sub-group analysis of a large multi-center real-world study/PROMISE from India - Wakhloo, Ajay; Maggo, Poonam; Menon, Tushna; Mehta, Jyotsna; Marathe, Umesh; Kulkarni, Ketan; Madkholkar, Nishikant; Tope, Rutuja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Real-world data on the efficacy and safety of intravenous ferric carboxymaltose (FCM) for treating iron deficiency anemia (IDA) in Indian women is limited. Methods: This was a sub-group analysis of the real-world PROMISE study, which analyzed data of women who received FCM for the management of IDA due to non-obstetric causes. Hematological parameters were retrieved from the charts at baseline and at 4±1 week and analyzed for the whole sub-group and by the severity of anemia. Results: In 442 women with anemia, Hb and serum ferritin improved by 2.77 gm/dl and 62.07 µg/l, respectively (p<0.001 for both) at 4 weeks. There was a significant increase in red blood cell (RBC) count, hematocrit, mean corpuscular volume (MCV), and mean corpuscular hemoglobin (MCH) (p<0.001 for all). In 192 subjects with severe anemia, there was a significant increase in Hb by 3.19 gm/dl, serum ferritin by 61.67 µg/l, RBC count, hematocrit, and MCV (p<0.001 for all); and MCH (p=0.002). In 226 subjects with moderate anemia, there was a significant increase in Hb by 2.41 gm/dl, serum ferritin by 62.75 µg/l, and MCV (p<0.001 for all); and MCH (p=0.003). No subject had mild anemia. No new safety signals or serious adverse events were reported. Physicians rated the efficacy and safety of FCM as very good to good in 94.1 and 94.2% of subjects, respectively. Conclusions: In Indian women, FCM effectively and safely corrects IDA due to non-obstetric causes, in a short span of 4 weeks.